D-beta-hydroxybutyrate protects neurons in models of Alzheimer's and Parkinson's disease. - Kashiwaya, Y; Takeshima, T; Mori, N; Nakashima, K; Clarke, K; Veech, R (2000)
The heroin analogue 1-methyl-4-phenylpyridinium, MPP(+), both in vitro and in vivo, produces death of dopaminergic substantia nigral cells by inhibiting the mitochondrial NADH dehydrogenase multienzyme complex, producing a syndrome indistinguishable from Parkinson's disease. Similarly, a fragment of amyloid protein, Abeta(1-42), is lethal to hippocampal cells, producing recent memory deficits characteristic of Alzheimer's disease. Here we show that addition of 4 mM d-beta-hydroxybutyrate protected cultured mesencephalic neurons from MPP(+) toxicity and hippocampal neurons from Abeta(1-42) toxicity. Our previous work in heart showed that ketone bodies, normal metabolites, can correct defects in mitochondrial energy generation. The ability of ketone bodies to protect neurons in culture suggests that defects in mitochondrial energy generation contribute to the pathophysiology of both brain diseases. These findings further suggest that ketone bodies may play a therapeutic role in these most common forms of human neurodegeneration.